(untitled) (Eurasian Journal of Ecology, 2023)
Forest ecosystems are one of the most important components of the Earth’s biosphere due to their global ecological and socio-economic importance. In hydromorphic landscapes of arid regions of Central Asia with its sharply continental climate, these ecosystems are represented by unique in their biodiversity and environment-forming role coastal tugay forests in river floodplains, flooded lowlands and islands. Among desert, semi-desert and steppe ecosystems, tugay forests are ecosystems with the highest aboveground biomass and biodiversity. Due to the growing reduction of runoff of most rivers in Central Asia due to increased water consumption by agrarian and industrial production and negative climatic changes, the area of tugay forest ecosystems has catastrophically decreased. Ecological restoration of degraded tugay forests is a key factor in combating desertification in arid regions. Taking into account the fact that tugay forest ecosystems are currently represented only by scattered areas exclusively in West and Central Asia, their conservation is of global importance. The results of a comprehensive study using remote sensing and GIS-technologies, field work to assess the successional dynamics of tugay ecosystems in the middle reaches of the Ili River in connection with hydrological and climatic factors are presented in the article. Key words: tugay ecosystems, remote sensing methods, vegetation degradation, climate change, river flow regulation, ecosystem conservation.